2008
DOI: 10.21273/hortsci.43.7.1975
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cold Tolerance in Blueberry Using EST Libraries, cDNA Microarrays, and Subtractive Hybridization

Abstract: To gain a better understanding of changes in gene expression associated with cold acclimation in the woody perennial blueberry (Vaccinium corymbosum L.) and ultimately use this information to develop more freeze-tolerant cultivars, a genomics approach based on the analysis of expressed sequence tags (ESTs) and microarrays was undertaken. Initially, two standard cDNA libraries, constructed using RNA from cold-acclimated (CA) and nonacclimated (NA) floral buds of the blueberry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These results were very similar to what we found previously using a small microarray to identify differentially expressed transcripts during cold acclimation/deacclimation [ 9 ]. Although the microarray was based on only about 1,500 unique genes [ 9 , 15 ], many of the transcripts identified as differentially expressed in that study were also identified as potentially differentially expressed in this study. Some of the transcripts identified as potentially downregulated during cold acclimation in both studies encoded dehydration-induced RD22-like protein/BURP domain-containing protein, certain heat shock proteins, certain dehydrins, beta-glucosidase, UDP-glucose dehydrogenase, and ascorbate peroxidase (Additional file 1 and [ 9 ]).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These results were very similar to what we found previously using a small microarray to identify differentially expressed transcripts during cold acclimation/deacclimation [ 9 ]. Although the microarray was based on only about 1,500 unique genes [ 9 , 15 ], many of the transcripts identified as differentially expressed in that study were also identified as potentially differentially expressed in this study. Some of the transcripts identified as potentially downregulated during cold acclimation in both studies encoded dehydration-induced RD22-like protein/BURP domain-containing protein, certain heat shock proteins, certain dehydrins, beta-glucosidase, UDP-glucose dehydrogenase, and ascorbate peroxidase (Additional file 1 and [ 9 ]).…”
Section: Resultsmentioning
confidence: 91%
“…Current mapping studies are focused on identifying quantitative trait loci (QTL) associated with chilling requirement, freezing tolerance, and fruit quality traits in blueberry. The first microarray experiments have been carried out in blueberry and have successfully identified many transcripts whose abundances increase with cold acclimation [ 9 , 15 ]. More gene expression studies need to be undertaken, however, that are based on a larger collection of gene sequences in order to sort out genes that are expressed in response to various stimuli and during development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the genome draft of a northern high-bush blueberry has been published [48,49]. The transcriptome analyses have been used for blueberry studies about characteristics of gene expression in the cold environment [50][51][52], the metabolics related genes of blueberry antioxidant substances [53], the changes of gene expression profiles in blueberry after infection with Colletotrichum acutatum [54], the gene expression dynamics during five blueberry fruit development stages [48], and detection of molecular markers [55]. However, the reports about the genome evolution of blueberry are limited.…”
Section: Introductionmentioning
confidence: 99%
“…This change was positively correlated with the total amount of soluble solids in the wood, which likely served as osmoprotectants able to reduce the freezing point. Inter-species differences in the level of expression of β-amylase genes in northern and southern highbush were described by Rowland et al ( 2008 ).…”
Section: Implications Of Climate Change On Blueberry Breedingmentioning
confidence: 90%